Proteomic insights into the environmental adaptation of the subtropical brain coral host Platygyra carnosa - Haiying Ma; Walter Dellisanti; Jeffery Tzu Hao Chung; Yilin Pan; Guopan Liu; Jiajun Wu; Jian-wen Qiu; Leo Lai Chan; Liang Zhang (iScience)
Summary: Despite the rapid coral reef decline from climate change, the molecular dynamics underlying coral environmental responses remain elusive. Filling this gap is vital to reef conservation. Here, we investigated the seasonal proteomes of Platygyra carnosa, a stress-tolerant subtropical brain coral, using natural samples across wet and dry seasons with distinct environmental conditions. Over 5,000 coral host proteins were profiled, revealing co-regulated modules related to temperature, pH, dissolved oxygen, salinity, and turbidity. Importantly, these modules formed scale-free networks coordinated by hub proteins that are strongly correlated with environmental drivers, suggesting their key roles in environmental adaptation. Laboratory validation confirmed the temperature-responsive hub proteins, including HSP90B1 and HSPA5 that modulate stress response and protein homeostasis. Our study characterized the brain coral host proteome with unprecedented depth, revealing co-regulated modules underlying environmental adaptation. It sets the stage for proteome-based approaches in promoting coral resilience, leading to more informed conservation and restoration efforts.